2012
DOI: 10.1007/s11356-012-0842-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α-Fe2O3 nanofibers for applications in removal and recovery of Cr(VI) from wastewater

Abstract: The as-prepared α-Fe(2)O(3) nanofibers can be utilized as efficient low-cost nano-absorbents for removal and recovery of Cr(VI) from wastewater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…Combination of various biopolymers with hematite is of high interest to scientists in over a range of fields [58], from the development of advanced drug carriers [59], targeted magnetic resonance imaging of tumors [60] to biosensors [56,61] supercapacitors [62], adsorbents [63,64] and catalysts for chemical reactions [65]. Several studies regarding the use of biological templates in hydrothermal synthesis of hematite have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of various biopolymers with hematite is of high interest to scientists in over a range of fields [58], from the development of advanced drug carriers [59], targeted magnetic resonance imaging of tumors [60] to biosensors [56,61] supercapacitors [62], adsorbents [63,64] and catalysts for chemical reactions [65]. Several studies regarding the use of biological templates in hydrothermal synthesis of hematite have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…where c e is the equilibrium concentration of CrO 4 2À in mg/L, q e is equilibrium adsorption capacity of CrO 4 2À on Fe 2 O 3 in mg/g, q m is the maximum adsorption capacity in mg/g, and b is the Langmuir equilibrium constant in L/mg (Ren et al, 2013). The equation can be modified to linearize the adsorption isotherm curve and yield a Fig.…”
Section: Adsorption Performancementioning
confidence: 99%
“…However, exposure to these contaminants continues around the world and increasingly in developing countries (Jarup, 2003). Chromium (Cr), an example of a carcinogenic heavy metal, is very common in diverse metal industry processes, such as electroplating, leather tanning, wood preservations and chemical industries (Chowdhury and Yanful, 2010;Ren et al, 2013). It has been reported that occurrences of Cr entering the environment are due to leakage, poor storage or unsafe disposal practices from such metal industry processes (Chowdhury and Yanful, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, nickel titanate is reported to be highly stable in oxidizing environment with visible light illumination which is crucial for the photocatalysis application [22,23] a-Fe 2 O 3 nanofibers were synthesized via a facile low temperature hydrothermal route followed by calcination in ambient air atmosphere [24]. A defined quantity of FeCl 3 Á6H 2 O (16 mmol) was dissolved in 112 mL deionised water to form a clear solution.…”
Section: Introductionmentioning
confidence: 99%